Addressing Weight Loss Recidivism: A Clinical Focus on Metabolic Rate and the Psychological Aspects of Obesity. (4th November 2012) - Grattan, Bruce J.; Connolly-Schoonen, Josephine
Abstract : Obesity in the United States has reached epidemic proportions and has become an unprecedented public health burden. This paper returns to the evidence for metabolic rate set points and emphasizes the clinical importance of addressing changes in metabolic rate throughout the weight loss process. In addition to the importance of clinically attending to the modulation of metabolic rate, the psychological aspects of obesity are addressed as part of the need to holistically treat obesity.